034. Arterials Re-Repair with Saphenous Vein Graft for Acute Limb Ischemia in Previously Repaired Patient: A Complicated Case Report - Trixie, Jessica (JBN (Jurnal Bedah Nasional), 2024)
Background : Acute upper extremity ischemia following trauma is a potentially limb-threatening condition that requires prompt diagnosis and intervention. We presented a complicated case of a patient who had previously undergone repair for his left arm but developed post-operative acute limb ischemia. Case: A 51-year-old male presented to the emergency room (ER) with acute numbness in his left hand. He previously underwent a muscle, artery, and nerve repair for his left arm due to a wooden impaled wound. Other comorbidities were denied, and the patient’s hemodynamics were stable. Physical examination showed left antebrachial covered with Backslab, tenderness upon palpation, and limited range of motion. The left fingers’ oxygen saturation were lower (90-93%). Left antebrachial imaging revealed no fracture. Vascular exploration, thrombectomy, and left radial and ulnar arteries repair using the saphenous vein graft were performed. The post-surgical outcome was great, and the numbness began to fade away. Left fingers’ oxygen saturation rose dramatically (94-95%). The patient was satisfied with the outcomes, followed by discharge from the hospital. Conclusion: Prompt recognition and surgical intervention of vascular trauma complications effectively restore function and alleviate symptoms.